Omnidirectional Configuration and Control Approach on Mini Heavy Loaded Forklift Autonomous Guided Vehicle - Norsharimie, Adam; Mohd, Aiman; Wan Mohd, Nafis; Addie Irawan, Hashim; Mohamad, Muaz; Mohamad, Hafiz; A. R., Razali; Sheikh Norhasmadi, Sheikh Ali (EDP Sciences, 2016)
This paper presents the omnidirectional configuration and control approach on Mini Heavy Loaded Forklift Autonomous Guided Vehicle (MHeLFAGV) for flexibility maneuverability in confine and narrow area. The issue in turning motion for nonholonomic vehicle in confine area becoming a motivation in MHeLFAGV design to provide holonomic vehicle with flexible movement. Therefore an omni-wheeled named Mecanum wheel has been configured in this vehicle design as well as omnidirectional control algorithm. MHeLFAGV system is developed with collaboration and inspired from Vacuumshmelze (M) Sdn. Bhd. Pekan, Pahang in order to have a customized mini forklift that able to work in a very confined warehouse (170cm x 270cm square) with heavy payload in a range of 20-200kg. In electronics control design, two stages of controller boards are developed namely as Board 1 and 2 that specifically for movement controller board and monitoring controller board respectively. In addition separate module of left, right, forward, backward, diagonal and zigzagging movement is developed as embedded modules for MHeLFAGV system’s control architecture. A few experiments are done to verify the algorithm for each omnidirectional movement of MHeLFAGV system in the wide area. The waypoint of MHeLFAGV movement is plotted using Global Positioning System (GPS) as well as a digital compass by mapping the longitude and latitude of the vehicle. There are slightly different between the targeted movements with recorded data since Mecanum wheeled affected by the uneven surface of the landscape. The experiment is also further on moving in confine are on the actual targeted warehouse.